2022
DOI: 10.1016/j.dib.2021.107732
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of Factors affecting online cheating by accounting students: The relevance of social factors and the fraud triangle model factors

Abstract: In this paper, the authors present survey data concerning to understand the motivations underlying the cheating behavior while university exams are held online during the Covid-19 pandemic. In pursuing its aims, this study uses an integrated theoretical framework that includes the social capital theory and the fraud triangle theory. Through the use of a previously tested questionnaire, this study gathers data concerning the students cheating behavior from 213 respondents across a group of Jordanian universitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 7 publications
1
29
0
2
Order By: Relevance
“…The variables in this study consist of the dependent variable, namely academic cheating behavior (FRAUD) whose statement indicators are taken from (Stone et al, 2010) and the independent variables, namely from the dimensions of the fraud triangle indicator taken from (Shbail et al, 2022) namely Pressure (PRESSURE), Opportunity (OPPORTUNITY), Rationalization (RATIONAL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables in this study consist of the dependent variable, namely academic cheating behavior (FRAUD) whose statement indicators are taken from (Stone et al, 2010) and the independent variables, namely from the dimensions of the fraud triangle indicator taken from (Shbail et al, 2022) namely Pressure (PRESSURE), Opportunity (OPPORTUNITY), Rationalization (RATIONAL).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, as there is no definite date yet on when full-time on-campus education will resume, this study tends to identify the motives behind cheating behavior during the pandemic. It is important to understand the factors that drive students to behave dishonestly in order to help educational institutions come up with a fair scoring system for student performance and to further take decisive action to reduce cheating in the future, which is likely to improve academic integrity among these institutions (Shbail et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…At the height of the pandemic period, academic dishonesty in Middle Eastern universities not only continued to prevail but it appears to have become even more widespread ( Al Shbail et al, 2021 ; Ebaid, 2021 ; Guangul et al, 2020 ). For example, Ebaid (2021) conducted a study among accounting students in Saudi universities and showed that cheating in online exams is a prevalent phenomenon as 93% of the participants reported that they had engaged in at least one incident of cheating during online exams.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Out of the distributed questionnaire copies, 815 were retrieved, of which 113 were deleted owing to missing data, making the remaining useable copies to be 702 – these were found to be valid to be exposed to statistical analysis. Prior to the actual data gathering, the questionnaire was developed in English and Arabic as both languages are considered to be formal languages in the universities in Jordan in the accounting faculty [1 , 2] .…”
Section: Data Descriptionmentioning
confidence: 99%